Peterson's stress concentration factors - Pilkey, Walter D.; Bi, Zhuming; Pilkey, Deborah F. (John Wiley & Sons, Inc., 2020)
"Peterson's Stress Concentration Factors establishes and maintains a system of data classification for all the applications of stress and strain analysis, and expedites their synthesis into CAD applications. Updated to reflect today's advances in stress and strain analysis, this book presents stress concentration factors both graphically and with formulas. The illustrated index allows readers to identify structures and shapes of interest based on the geometry and loading of the location of a stress concentration factor. This Fourth Edition includes a thorough introduction of the theory and methods for static and fatigue design, quantification of stress and strain, research on stress concentration factors for weld joints and composite materials, and a new introduction to the systematic stress analysis approach using Finite Element Analysis (FEA)"--